Clinical and molecular characterisation of Bardet–Biedl syndrome in consanguineous populations: the power of homozygosity mapping. Issue 4 (26th October 2009) - Abu Safieh, L; Aldahmesh, M A; Shamseldin, H; Hashem, M; Shaheen, R; Alkuraya, H; Al Hazzaa, S A F; Al-Rajhi, A; Alkuraya, F S
Abstract : Bardet–Biedl syndrome (BBS) is a ciliopathy with pleiotropic effect that manifests primarily as renal insufficiency, polydactyly, retinal dystrophy and obesity. The current phenotype–genotype correlation is insufficient to predict the likely causative mutation that makes sequencing of all 14 BBS genes an often necessary but highly complicated way to identify the underlying genetic defect in affected patients. In this study, homozygosity mapping is shown as a robust approach that is highly suited for genetically heterogeneous autosomal recessive disorders in populations in which consanguinity is prevalent. This approach allowed us to quickly identify seven novel mutations in seven families with BBS. Some of these mutations would have been missed by unguided routine sequencing, which suggests that missed mutations in known BBS genes could be more common than previously thought. This study, the largest to date on Saudi BBS families, also revealed interesting phenotypic aspects of BBS, including the first report of non-syndromic retinitis pigmentosa as a novel BBS phenotype.